2019
DOI: 10.7554/elife.46754
|View full text |Cite
|
Sign up to set email alerts
|

The role of structural pleiotropy and regulatory evolution in the retention of heteromers of paralogs

Abstract: Gene duplication is a driver of the evolution of new functions. The duplication of genes encoding homomeric proteins leads to the formation of homomers and heteromers of paralogs, creating new complexes after a single duplication event. The loss of these heteromers may be required for the two paralogs to evolve independent functions. Using yeast as a model, we find that heteromerization is frequent among duplicated homomers and correlates with functional similarity between paralogs. Using in silico evolution, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 120 publications
(207 reference statements)
2
45
0
Order By: Relevance
“…Analyzing human, Arabidopsis, yeast and E. coli protein-protein interaction (PPI) data, [3] reported that most oligomeric paralogs diverged to form obligatory homomers. However, analysis of yeast, worm and fly, using both PPI data and oligomers of known structure, [2] indicated that heteromeric interactions dominate, a conclusion recently supported by [4] who analyzed yeast PPI data. We compared these studies and observed that these inconsistencies relate to three major factors.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Analyzing human, Arabidopsis, yeast and E. coli protein-protein interaction (PPI) data, [3] reported that most oligomeric paralogs diverged to form obligatory homomers. However, analysis of yeast, worm and fly, using both PPI data and oligomers of known structure, [2] indicated that heteromeric interactions dominate, a conclusion recently supported by [4] who analyzed yeast PPI data. We compared these studies and observed that these inconsistencies relate to three major factors.…”
Section: Introductionmentioning
confidence: 85%
“…Duplication is also ubiquitous and hence serves as the main source of new genes/proteins, as manifested by nearly half of all genes in a given genome being paralogs [1]. The duplication of genes encoding an oligomeric protein is of particular interest-the ancestral function may diverge alongside the oligomeric state thus providing new opportunities for evolutionary innovation [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, coevolutionary analysis generally results in contacts predicted at the whole family level, thus predicting contact maps putatively formed by any member of the protein family. However, for large families consisting of multiple subgroups (or subfamilies), gene duplication and specialization lead to structural and functional variability of paralogous proteins sharing the overall same fold, but potentially carrying a sub-set of different contacts defining subfamily specificities [18,19]. Similarly, organisms with different genetic backgrounds and evolving in different environments will be subject to different fitness landscapes, thus not necessarily requiring the exact same structural and functional features, while still maintaining the same overall fold and function [20,21].…”
Section: Introductionmentioning
confidence: 99%